Drainage of Buildings and Territories in Conditions of Low Permeable Soils - Galina Kliorina; Marina Lapshina (European Scientific Journal, ESJ, 2017)
This article shows specialty of the substantiation for optimum parameters of drainage systems in the low permeable soil for buildings and territories. This paper lists significant factors of a choice of the key parameters which defines the efficiency of drainage systems. It is being given their role in decision-making for geotechnical conditions of the Northwest region of Russia. The analysis is made for the drainage servicing objects with burying of the exploited volumes in limits of 6-7 meters. This article describes various features of the drainage of territories and buildings with a big area of the equipped permeable surfaces. It investigates significant factors for the choice of effective system of drainage: water drawdown power, texture of a geologic profile, structural-spatial concept of buildings, technological and environmental requirements, and safety regulations. This article shows dependence between each factor and parameters of drainage: constructional type, situation in the plan, an overhang confining layer, and water handling construction. The report notes that practice testifies to the requirement of the use of the complicated schemes and the drainage construction of drainage without pipe. This is in connection with increase in safety requirements and ecology.